Unraveling the after-hours dilemma: Consequences of overworking among teleworkers—A scoping review protocol - Bao-Zhu Stephanie Long; Kishana Balakrishnar; Luke A. Fiorini; Aaron Howe; Ali Bani-Fatemi; Basem Gohar; Behdin Nowrouzi-Kia (PLoS ONE, 2025)
Background Telework, also referred to as telecommuting, remote work, flexible work, and virtual work, involves working from a location different from the traditional office and often uses online communication technologies. Despite the numerous advantages associated with teleworking, it also raises concerns about work-life balance and health implications due to working after hours (WAH). Objective This proposed study aims to understand the health consequences of teleworkers working beyond their scheduled hours. Methods This review will search seven online databases (APA PsycINFO, Medline, Embase, Scopus, Business Source Premier, CINAHL, and Sociological Abstracts) to gather relevant articles. The inclusion criteria will encompass peer-reviewed studies published from 2010 onwards, focusing on WAH among teleworkers and reporting mental and physical health consequences. The exclusion criteria will include non-peer-reviewed articles, grey literature, and studies involving patients with pre-existing conditions. Discussion This review will provide valuable insights into the mental and physical health consequences of WAH among teleworkers, underscoring the urgent need for strategies to mitigate these risks and promote overall well-being. Future efforts, including collaborations between researchers, industry leaders, and policymakers, can guide the development of targeted interventions and evidence-based policies that improve telework environments and support long-term worker health and productivity.